Pengaruh Kepercayaan Konsumen, Kemudahan Penggunaan, dan Fleksibilitas Pembayaran TikTok PayLater terhadap Keputusan Pembelian Kosmetik Wardah (Studi Kasus pada Mahasiswa Universitas Prof. Dr. Hazairin, SH Bengkulu) - Nesti Nesti; Syofian Syofian; Janusi Waliamin (ARZUSIN, 2025)
This study aims to examine the influence of consumer trust, ease of use, and payment flexibility of TikTok PayLater on purchasing decisions for Wardah cosmetics. The research employed a quantitative explanatory approach, designed to explain relationships and effects among variables. The sampling technique used purposive sampling, with the population being students of Universitas Prof. Dr. Hazairin, SH Bengkulu. A total of 120 respondents who had used TikTok PayLater and purchased Wardah cosmetics online were selected. Primary data were collected through an online questionnaire distributed via Google Forms using a Likert scale, and analyzed with SPSS version 25. The results show that, partially, consumer trust, ease of use, and payment flexibility each have a significant effect on purchasing decisions. Simultaneously, these three variables also significantly influence purchasing decisions for Wardah cosmetics. These findings affirm that the integration of psychological (trust), functional (ease of use), and financial (payment flexibility) aspects plays an important role in driving purchasing decisions in the digital era. The study concludes by emphasizing the importance of marketing strategies that are responsive to digital consumer behavior. The implications suggest that these results may serve as a reference for designing technology-based marketing strategies in the cosmetics industry as well as in the broader e-commerce sector.